Chemistry Students’ Awareness and Interest on Usage of Chemical Concepts Knowledge in Tie & Dye for Entrepreneurial Skills Development in Kwara State - AKANBI, Ganiyu Adedo; OMONIYI, Olubunmi Adesoji (Ilorin Journal of Education, 2024)
Entrepreneurship awareness and interest are part of basic necessities for average chemistry students that direct their minds towards entrepreneurship development after school which is capable of reducing unemployment, poverty and other social vices within the society. The study is to determine the awareness and the interest of chemistry students on the usage of chemical concepts in tie and dye for entrepreneurship skills development in Kwara State. The populations were all science students in the public secondary schools in Kwara state and the sample consisted of 110 SSII science students. Two instruments are used in collection of data. A pilot test was conducted involving 20 non participants and the reliability coefficient of r = 0.82 and r - 0.83 was establish using Cronbach Alpha. Research questions were answered using means and standard deviation while research hypotheses were tested at p = 0.05 using t-test. The results showed that there is significant difference in the male and female awareness and interest at (p>0.05)). The study concluded that male and female secondary school students in Kwara State have high awareness and interest on the usage of knowledge of chemical concepts in tie and dye for entrepreneurship skills development in Kwara State. The study therefore recommended that there is an urgent need for the government and education stakeholders to develop a comprehensive framework to see how entrepreneurship skills acquisition could be part of core course in the chemistry school curriculum and teacher should see chemistry teaching beyond the classroom situation.